A Study of bullying among students in a high school in Pathum Thani Province - Bhagavasopit, Jakkitinan; Khrukham, Seksan (Journal for Developing the Social and Community, 2025)
Background and Aims: Bullying in educational institutions is a significant issue that affects students’ emotional and social development as well as their interpersonal relationships. It can cause psychological trauma and have long-term consequences throughout their future lives. The objectives of this study are: 1) To examine bullying behaviors among students in a secondary school in Pathum Thani Province; 2) To investigate the factors associated with bullying behaviors among students in a secondary school in Pathum Thani Province; and 3) To identify appropriate strategies for educational institutions to prevent and address bullying behaviors among students in a secondary school in Pathum Thani Province. Methodology: A mixed-methods approach was employed. The quantitative sample consisted of 250 lower secondary students selected through simple random sampling, while the qualitative data were collected through in-depth interviews with 13 teachers, school administrators, psychologists, and relevant personnel. Research instruments included a questionnaire and a semi-structured interview. Quantitative data were analyzed using descriptive and inferential statistics, and qualitative data were analyzed through systematic content analysis. Results: 1) Verbal bullying is the most common form, followed by physical and psychological bullying. Perpetrators often hold influence within their peer groups, while victims tend to isolate themselves and avoid retaliation. 2) Significant associated factors include gender, previous experiences of being bullied, association with aggressive peers, and low self-control. And 3) Practical strategies for schools to prevent and address bullying behaviors include establishing school regulations that cover all forms of bullying, organizing activities to enhance self-control and emotional management, promoting respect for diversity, implementing a monitoring system and secure reporting channels, and providing continuous follow-up and individualized behavioral adjustment. Conclusion: Preventing and addressing bullying in schools cannot rely solely on any single measure or project. It requires the collaboration of all stakeholders including teachers, administrators, students, parents, and relevant personnel to collectively foster a safe, supportive, and emotionally nurturing learning environment. Schools should be spaces where every student feels respected, understood, and protected when facing problems. At the same time, efforts should be made to cultivate a culture of empathy, mutual respect, and acceptance of diversity in a sustainable way.